👤

Rozwiąż równania:
2x-3 = 5x-2
3(x-1) - 2(2-3x) = 3x-3
X - 1-x3 =1
-412x – 5 = -14
- 34 - 14 x = 2,25


Odpowiedź :

1) 2x-3 = 5x-2

2x - 5x = -2 + 3

-3x = 1   / : -3

x = - 1/3

2) 3(x-1) - 2(2-3x) = 3x-3

3x - 3 - 4 + 6x = 3x - 3

-4 + 6x = 0

6x = 4   / : 6

x = 2/3

3) X - 1-x3 =1

x - 1 - 3x = 1

-2x - 1 = 1

-2x = 1 + 1

-2x = 2   / : -2

x = -1

4) -412x – 5 = -14

412x = -14 + 5

412x = -9   / : 412

x = - 9/412

5) - 34 - 14 x = 2,25

-14x = 2,25 + 34

-14x = 36,25   / : -14

x = - 145/56 = -2 33/56